Response and Impact of the Covid-19 Pandemic on Mathematics Education Students - Prasetyo, Yohannes Eko; Darmadi, Darmadi (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2021)
Large Scale Social Restrictions (PSBB) due to the outbreak of the Covid-19 pandemic have raised significant problems for the world of education. The impact received by students is very large, especially mathematics education students. Subjects that are known to be difficult need to be studied properly by students. So that it creates psychological pressure on individual students. The method used in this research is data collection through interviews and questionnaires. This study aims to determine the impact of government-issued policies, namely online learning.